Kinematyka Ośrodka Sypkiego na Przykładzie Wciskania Płaskiego Stempla - Drescher, A.; Bujak, A. (Engineering Transactions, 1966)
This is a discussion of the results of an experimental work consisting in indenting with a plane punch a granular body under the conditions of limit equilibrium. The state of strain is plane. The experiments have been carried out using a box filled up with only one kind of sand of constant density and two kinds of punches under prescribed kinematics conditions i.e. thatof constant velocity of penetration of the punch. The pressure was recorded in function of the depth, as well as the displacement field of soil particles, the latter record being performed by the photographic method. The velocity field was obtained from the displacement field in function of pressure and indentation depth.The results of the experiments are confronted with the theoretical results obtained for a kinematically and statically admissible field, taking into consideration the weight of the body. This confrontation shows that the kinematically admissible field computed by assuming the associated flow law does not represent the velocity field obtained experimentally.